NUMERICAL ANALYSIS OF GILL AND COOLING DUCT ADDITION ON SIDEPOD OF FORMULA STUDENT RACING CAR TYPE - Fauzun, Fauzun; Yudhistira, Thareq Akbar Arya; Yogiswara, Cahyo Wibi; Hidayat, Akbar Fadhlurrohman (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2025)
Formula Student SAE (FSAE) car is designed to optimize the engine performance to achieve maximum power. To get the maximum power, the work of the car is very vulnerable to over-heating problems. Prevention step of overheating problems can be done by optimizing radiator cooling system performance. It is needed a design that can maximize radiator cooling performance by maximizing the supply of airflow through the radiator using the aerodynamic system in the car. The sidepod geometry with the addition of gills and cooling duct is specifically investigated to produce best airflow to maximize radiator cooling performance and optimize the car's aerodynamic system. This research investigates how modifications to the sidepod geometry, including the addition of gills and cooling ducts, can improve airflow and heat transfer to maximize radiator cooling performance and enhance the car's aerodynamic system. The value of the heat transfer rate, lift coefficient, and drag coefficient of the car were investigated using ANSYS Fluent. Furthermore, the Existing Sidepod design was evaluated and the results will be taken as the forthcoming development of the new sidepod designs. Adding geometry to the sidepod proves can affect the value of the heat transfer rate, lift coefficient, and drag coefficient. The addition of geometry in the form of outlet gills and cooling duct has been proven to increase the value of heat transfer rate and reduce the value of lift coefficient and drag coefficient. While the addition of inlet gills only increases the value of the heat transfer rate and reduces lift coefficient without reducing drag coefficient. The best performance from all aspects reviewed was obtained by giving geometry on the sidepod is the outlet gills. This method offers a novel approach to optimizing sidepod designs in Formula Student Cars, contributing to both performance and efficiency advancements.